2023
DOI: 10.1142/s0129055x2350006x
|View full text |Cite
|
Sign up to set email alerts
|

Bogoliubov dynamics and higher-order corrections for the regularized Nelson model

Abstract: We study the time evolution of the Nelson model in a mean-field limit in which [Formula: see text] nonrelativistic bosons weakly couple (with respect to the particle number) to a positive or zero mass quantized scalar field. Our main result is the derivation of the Bogoliubov dynamics and higher-order corrections. More precisely, we prove the convergence of the approximate wave function to the many-body wave function in norm, with a convergence rate proportional to the number of corrections taken into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Our article is an application of that expansion for the ground state energy. Note that the work [6] was in turn inspired by an analogous result for the dynamics [5]; see also the follow-up work [7]. Let us refer to [2] and [3] for reviews of both results, and note that in [4] the results from [6] are applied to derive an Edgeworth expansion for the fluctuations of bounded one-body operators with respect to the ground state and low-energy excited states of the weakly interacting Bose gas.…”
Section: Introduction and Main Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Our article is an application of that expansion for the ground state energy. Note that the work [6] was in turn inspired by an analogous result for the dynamics [5]; see also the follow-up work [7]. Let us refer to [2] and [3] for reviews of both results, and note that in [4] the results from [6] are applied to derive an Edgeworth expansion for the fluctuations of bounded one-body operators with respect to the ground state and low-energy excited states of the weakly interacting Bose gas.…”
Section: Introduction and Main Resultsmentioning
confidence: 95%
“…with initial datum (ϕ 0 , α 0 ), where |ϕ(t)| 2 is the Fourier transform of |ϕ(t)| 2 . In [21] it was shown that (for suitably chosen initial states) the time evolution of the regularized Nelson model satisfies an asymptotic expansion in the spirit of Theorem 4. The main difference to the previous subsection, where N bosons interact via pair potentials, is that the system consists now of two types of particles.…”
Section: Regularized Nelson Modelmentioning
confidence: 99%
See 2 more Smart Citations